Work pattern in Forensic Medicine: Challenges to Changes during COVID19 pandemic - Kumar Vidua, Raghvendra; Arora, Arneet; Bhargava, Daideepya C; Kumar Chouksey, Vivek; Jana, Rituparna; Dwivedi, Ankit (Journal of Indian Academy of Forensic Medicine, 2021)
COVID-19 pandemic has drastically changed the prevailing practices in almost all the disciplines of Medical Sciences and the Forensic medicine could also not bear to be remained isolated to such changes. The old age practice in Forensic Medicine in form of conducting the autopsy has been changed and it is being avoided in COVID positive as well as brought dead cases as much as possible. Now it is being largely limited only to the cases where it can’t be avoided and that too in minimally invasive form, following all govt protocols while under the umbrella of full biosafety measures. Due to lockdown measures as people are staying at their home, the workload in form of autopsy on accidental, suicidal and homicidal deaths has been drastically reduced but it has been increased on other side where a larger number of COVID positive deaths are coming up which covers aspect ranging from it’s risk reducing management to safe disposal. With the high risk involved in dealing with those bodies and emerging challenges of prevention from contracting disease, now this discipline is also learning to work with riskier procedures under psychological fear of infection and adapting to work under new conditions.